2018
DOI: 10.1111/joca.12202
|View full text |Cite
|
Sign up to set email alerts
|

Are Ex‐Ante Hypothetical Bias Calibration Methods Context Dependent? Evidence from Online Food Shoppers in China

Abstract: Consumers are increasingly turning to the Internet as a medium of acquiring food products. This study informs the consumer literature by assessing the effects of three ex‐ante hypothetical bias mitigation methods on Chinese consumer's stated online food shopping behavior: a cheap talk script, the solemn oath, and honesty priming. Using data from choice experiments (CEs), our analysis finds no significant differences in willingness to pay (WTP) values for select product attributes (origin, product rating, and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 69 publications
1
14
0
Order By: Relevance
“…Further, in line with previous food choice studies (e.g. Bazzani et al, 2017;Lin et al, 2019), we tested whether the differences in WTP between treatments are statistically significant using hypothesis tests of equality across treatments. Based on our research hypotheses, we did so by using a between-subject pooled data approach based on the cross-treatment comparisons of: (i) Control vs. GENE; (ii) GENE vs. GENE-GMO; (iii) GENE vs. GENE-AW; and (iv) GENE-AW vs. GENE-GMO-AW.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, in line with previous food choice studies (e.g. Bazzani et al, 2017;Lin et al, 2019), we tested whether the differences in WTP between treatments are statistically significant using hypothesis tests of equality across treatments. Based on our research hypotheses, we did so by using a between-subject pooled data approach based on the cross-treatment comparisons of: (i) Control vs. GENE; (ii) GENE vs. GENE-GMO; (iii) GENE vs. GENE-AW; and (iv) GENE-AW vs. GENE-GMO-AW.…”
Section: Discussionmentioning
confidence: 99%
“…Although animal welfare in general is perceived as a highly important attribute by consumers (see, e.g., Lagerkvist and Hess, 2011 for a review), consumer WTP for milk from gene-edited dehorned cows will be limited unless consumers view the gene-editing technology as a tool to enhance animal welfare. As such, the communication of inherent benefits plays a pivotal role in determining consumer WTP for food from gene-edited animals, and indeed prior studies have shown that consumer acceptance of new food technologies can partly be shaped by the type of information consumers receive about those products (Hoban, 1998;Lusk et al, 2004;Delwaide et al, 2015;Edenbrandt et al, 2018;Shew et al, 2018;Lin et al, 2019). However, these studies are mostly limited to focus on plant-based products and/or GM products.…”
Section: Introductionmentioning
confidence: 99%
“…All the remaining terms are the same as in Equation (1). Finally, following previous research where a betweensubject treatments approach was implemented (e.g., Alemu & Olsen, 2018;Bazzani et al, 2017;de-Magistris, Gracia, & Nayga, 2013;Lin, Ortega, & Caputo, 2018), we ran pooled models using responses from control and treatment group pairs as a robustness test of the impact of information on mWTP formation. All models were estimated using functions from the "gmnl" package for R (Sarrias & Daziano, 2017).…”
Section: Econometric Analysis Of Rcementioning
confidence: 99%
“…Despite these studies, there are still ample opportunities for future research in this area especially in the context of online grocery markets. For example, it may be interesting to replicate this article in other platforms such as eBay and Walmart or in other markets, as conducted in China by Lin, Ortega, and Caputo (2018). It may also be interesting to investigate interaction effects of the attributes of the distribution of online ratings as well as other components of the online consumer reviews that are becoming important over time, such as helpful votes, top reviews, review dates, answered questions, and so forth and how these attributes affect grocery sales.…”
Section: Conclusion and Directions For Future Workmentioning
confidence: 92%